Use, indications and diagnostic yield of implantable loop recorder in clinical practice: a single, high volume, tertiary care centre experience. (25th November 2020) - Castagno, D; Donadoni, M; Golzio, P.G; Budano, C; Anselmino, M; Ferraris, F; Jorfida, M; Bissolino, A; Magnano, M; Gagliardi, M; Di Summa, R; Ruffini, S; et al.
Abstract: Introduction: Besides the established class I indication for the evaluation of patients with recurrent syncope of uncertain origin, implantable loop recorders (ILRs) have been increasingly used for other diagnostic purposes (e.g. detection of atrial fibrillation (AF) following cryptogenic stroke). Purpose: To describe the main indications to ILR and to investigate procedural parameters, outcomes and diagnostic yield of ILR in a single, high-volume tertiary care centre. Methods: All patients undergoing ILR implantation between October 2010 and October 2019 were consecutively enrolled in this study. Clinical characteristics of patients, procedural data and outcomes were collected. The indications to ILR implantation were divided into four categories: 1) AF detection in patients with recent cryptogenic stroke or peripheral thromboembolism [CRYSP], 2) recurrent syncope of uncertain origin [RSUO], 3) monitoring of ventricular arrhythmic events [VAE] in patients with predisposing cardiomyopathy/channelopathy, 4) monitoring of AF burden [AFB]. The main endpoint of the study was the diagnostic yield (number of definitive diagnoses made) and the time to diagnosis following ILR implantation. The occurrence of acute or subacute complications was used as a secondary safety endpoint. Results: Overall, 1008 patients underwent ILR implantation (mean age 64 years, 43% female). The two main indications to ILR were AF detection following CRYSP and RSUO (41% and 34% of all implantations respectively, table 1). The commonest site of implantation was the left parasternal position (570 patients, 57%), median procedural time was 20 minutes (IQR 15–25). During a median follow-up of 580 days (186–1179), a definitive diagnosis was achieved in 366 (36%) patients after a median time of 208 days (IQR 59–515) [table 1 shows details and action taken following diagnosis for each indication subgroup]. Infections requiring ILR extraction or pocket revision occurred in 12 patients (1.2%). Conclusions: In this cohort of patients use of ILR was associated with a good diagnostic yield regardless of the initial indication, triggered timely therapeutic actions and was overall safe. Funding Acknowledgement: Type of funding source: None